Kinship and Transborder Exchange at the Bulgarian-Serbian border in the second half of the 20th century - Galia Valtchinova (European Journal of Turkish Studies)
The paper explores the nature and the varieties of transborder encounters on the Bulgarian-Serbian border during socialism and the first post-socialist decade. It offers some facts, and analyzes processes showing what happens when family and kinship have been politicized and manipulated, both on the level of existing structures and as symbols. A historical sketch and an overview of the local structures of kinship provide avenues for understanding the importance of the uses of kinship in a border society and the discourse of ‘being the same kin’ with people on the other side of the border. The ritual and effective uses of kinship in the peculiar conditions of State socialism are analyzed in the second part of the paper. The third and most lengthy part is dedicated to the post-socialist transformations in the visions of kinship and to some patterns of the use of kin in the context of ‘liberal market’ economy. I hope having shown that the visions of how to ‘use’ of family ties – and whether to use them, or not – could considerably change over time, especially when there was an ideological and political pressure to do this. Thus in late socialist period, the ideology and images of kinship were used by the communist State in order to counter practices like black market or border petty trade that could not be dissolved in the ideological dogmas. The moralization and politicization of kinship promoted under socialism, but also in the pre-communist period, had an impact on the development of transborder trade in recent years: in lieu of the expected ‘ethnic’ networks based on a working kin system, the booming transborder trade and smuggling led to the constitution of trans-ethnic networks between ethnic Bulgarians and local Roma. The latter assumed the tasks that both the discourses of kinship and the socialist value system tended to blame as shameful. The recent developments under review call for a more careful consideration of what kind of ‘family’, for what kind of ‘networks’, are used during a post-socialist transition.